2003
DOI: 10.1161/01.hyp.0000051501.20424.5d
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyl Cyclase Receptors Mediate Cardiopulmonary Vagal Reflex Actions of ANP

Abstract: Abstract-Atrial natriuretic peptide (ANP) potentiates vagal cardiopulmonary reflexes due to chemosensory (BezoldJarisch [B-J] reflex) or mechanosensory (ramp baroreflex) activation. The ANP receptor mediating these actions is unknown. We examined the role of particulate guanylyl-cyclase (pGC) receptors in ANP-induced enhancement of cardiopulmonary vagal reflexes. Cardiopulmonary baroreceptor reflex function was assessed by bradycardic responses to ramp blood pressure rises after rapid intravenous methoxamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 45 publications
1
23
1
2
Order By: Relevance
“…This does not, however, rule out the possibility that old rats have some modest deficit in the basal level of natriuretic peptide signaling, which we have shown to be necessary for the full expression of the BJR. 19 Many other mechanisms could underlie the reduced reflex responsiveness of older rats, however, and the issue awaits direct study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not, however, rule out the possibility that old rats have some modest deficit in the basal level of natriuretic peptide signaling, which we have shown to be necessary for the full expression of the BJR. 19 Many other mechanisms could underlie the reduced reflex responsiveness of older rats, however, and the issue awaits direct study.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,18,19 Briefly, (1) ramp baroreflex responses were assessed after rapid MAP increases of approximately 50 mm Hg evoked by methoxamine (100 g/kg intravenously; Sigma Chemical) aiming for a similar rate of MAP rise across all animals (approximately 20 mm Hg/s). Linear regression analysis was applied to the progressive HR responses to MAP changes.…”
Section: Hr Reflex Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The action of BNP, as well as ANP and, to a lesser extent, CNP to enhance the von Bezold-Jarisch reflex bradycardia, is well established (22)(23)(24)(25): this action is mediated by particulate GC receptors since it is blocked by the pGC-receptor antagonist HS-142-1 (25). The site of this action of BNP and the other natriuretic peptides has been inferred to be on cardiac afferents.…”
Section: Discussionmentioning
confidence: 99%
“…This action has been shown in several species and may be produced by all three natriuretic peptides, although BNP is the most potent (23,27). This action is mediated by particulate guanylate cyclase (pGC) receptors (25), but their location is as yet uncertain. On the one hand, experiments on rats and sheep have found that BNP, in a dose that enhanced the von BezoldJarisch and "ramp" (cardiac) baroreflex, did not alter the bradycardic response to arterial baroreceptor loading [as assessed by the steady-state baroreceptor reflex (26,27)].…”
mentioning
confidence: 99%